Malaysia : Staff Report for the 2013 Article IV Consultation. - International Monetary Fund. Asia and Pacific Dept. (Washington, D.C. : International Monetary Fund, 2014)
The IMF staff report for the 2013 Article IV Consultation focuses on Malaysia's economic developments and policies. The IMF report discusses that continued growth in domestic demand, especially investment, and a pickup in external demand should help maintain robust growth going forward despite the fiscal tightening. Amidst concerns about Malaysia's public finances and sharp narrowing of the external surplus in spring-summer of 2013, authorities have taken timely action to secure fiscal sustainability and assure markets. It suggests that authorities' decisions in 2013 are close to a fiscal policy breakthrough aiming to contain federal debt and related fiscal risks.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet